EKSTRAKSI KULIT BATANG ROSELLA (Hibiscus sabdariffa L.) SEBAGAI PEWARNA MERAH ALAMI - Mardiah, Mardiah (JURNAL PERTANIAN, 2010)
Colors are used to give more interesting appearance. Rosella (Hibiscus sabdariffa) flower is a natural color source as its red-colored flower contains high anthocyanin.The study was done in three stages. In the first stage, an extraction of anthocyanin pigment from Rosella bark was done. The treatments given in this study were to levels of extraction temperatures, namely room temperature and 60oC. The types of acids used included citric, succinic, oxalic, malic, and asetic acids. In stage 2, the acid that gave the best extraction result in stage 1 was used in different rates, namely 0.25, 0.5, and 0.75%. To determine the best extraction solvent, three solutions namely aquadest (A) and a combination of aquadest and ethanol (B) were used.Results showed that extraction temperature that gave the best anthocyanin rate was 60oC. The acid that produced the best extraction of bark and petals was 0.5% malic acid. Meanwhile, the combination of aquadest and 95% ethanol was found to be the solvent that gave the best result.